The Correlation between Eating Behavior and Nutritional Status in Senior High School Adolescents - Khoerunida, Riani; Sari, Sheizi Prista; Amira, Iceu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Indonesia has experienced triple burdens of malnutrition characterized by undernutrition, overweight, and micronutrient deficiency problems. Adolescents are vulnerable population for these kind of problems because they tend to change theirs eating behavior along with physical and psychological development. This study aim to determine the correlation between eating behavior and nutritional status in adolescents at SMAN 22 Bandung. A cross-sectional design was used for the study, involving 277 participants randomly chosen from the population. Eating behavior variable was assessed using a modified version of the Dutch Eating Behaviour Questionnaire (DEBQ) which comprised 28 items covering restrained, emotional, and external aspects of eating behavior. Nutritional status was determined based on Body Mass Index (BMI). The Spearman Rank correlation test was used for bivariate analysis. Aspects of restrained eating behavior and external eating behavior significantly correlated with nutritional status with the value of (p = 0.003, r = 0.173) and (p = 0.003, r = -0.176) respectively. Meanwhile, there is no significant correlation between emotional eating behavior with nutritional status (p = 0.166, r = 0.081). Restrained eating behavior showed a positive correlation, indicating that individuals exhibiting higher levels of restrained eating behavior tended to have over-nutritional status. Conversely, external eating behavior demonstrated a negative correlation, suggesting that higher levels of external eating behavior were associated with poorer nutritional status.